Puppets, Actors and Directors: Edward Gordon Craig and the Euopean Avant-garde - Olga Taxidou (Miscelánea: A Journal of English and American Studies)
This essay reads the work of Edward Gordon Craig within the tradition of the European theatrical avant-garde. Though he is hailed as one of the "prophets" of twentieth-century theatre, Craig and his overall project are almost never read within their historical and ideological context. Rather than viewing his work as an exception within the mainly literary experiments in Anglophone modernist theatre, this essay proposes a reading that finds parallels between Craig and his European contemporaries. Craig's view of the "art of the theatre" as a distinct discursive practice and not as an extension of literature, places him alongside figures like Reinhardt, Stanislavsky, Meyerhold and Artaud. In particular, this essay reads the work of Meyerhold against that of Craig. It attempts to treat the two directors/ visionaries as "test-cases", as they express similar aesthetic preoccupations on opposite extremes of the political spectrum (Meyerhold was a "utopian" Marxist and Craig flirted with fascism). Both men admired each other's work. Craig's aphoristic writings on the role of the actor are read in conjuction with Kleist' s romantic essay on marionettes. This essay was first published in English by Craig in his journal The Mask (1909-1929), which also partakes in the avant-garde tradition of the manifesto. Rather than being a unique and solitary figure on an otherwise literary landscape, Craig is seen as forming part of the diverse and revolutionary spirit that was the European avant-garde in the early decades of this century.